ELECTRICAL ENERGY OUTPUT OF A WAVE-ACTIVATED BUOY ENERGY CONVERTER SYSTEM IN TATAR, WEST SUMBAWA - Aditya Pratama, Achmad
The implementation of renewable energy resources to satisfy the electrical needs and in effort of reducing carbon emission in Indonesia has been halted due to its higher invest value. Wave-activated buoy technology is the chance needed to implement renewable ocean wave energy because of its lower invest value. The plan to implement wave-activated buoy system in Tatar, West Sumbawa, NTB is considered to reduce the electricity cost and to maximize the invest’s return value. This final project aims to determine the electrical energy output of a wave-activated buoy in various regular wave conditions in regards to Tatar’s enviromental data. The project is done by identifying Tatar’s enviromental data and through hydrodynamic modelling based on the parameter of the existing waves. The system is then modelled with moorings by determining the moorings’ properties that is in line with the maximum mooring tension value discussed in the article made by Nam, Sung, and Cho (2021). The moorings’ properties, displacement and velocity of the system, as well as regular waves’ probabilities are used to calculate the electrical power and energy that is produced by the system. From various cases, it is known that large value of energy is produced from regular waves with ???? = 1 ? 3 ???? and ???? = 4 ? 13 ???? , but the highest energy value is ???????????????????????????? = 5.047 ???????????? which is produced from a wave with ???? = 2 ????, ???? = 9 ???? and the total annual energy reaches 94.1 ???????????? . It is also determined that the average efficiency of the system is 3.475% with a 0.711% capacity factor.